2017
DOI: 10.1002/nbm.3778
|View full text |Cite
|
Sign up to set email alerts
|

A review of diffusion MRI of typical white matter development from early childhood to young adulthood

Abstract: Understanding typical, healthy brain development provides a baseline from which to detect and characterize brain anomalies associated with various neurological or psychiatric disorders and diseases. Diffusion MRI is well suited to study white matter development, as it can virtually extract individual tracts and yield parameters that may reflect alterations in the underlying neural micro-structure (e.g. myelination, axon density, fiber coherence), though it is limited by its lack of specificity and other method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
298
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(343 citation statements)
references
References 167 publications
(340 reference statements)
21
298
6
Order By: Relevance
“…While most regions and measures showed linear trends, quadratic models outperformed linear models for MD in the splenium, and NDI in all regions except the right IFOF, right CST, and splenium, however, quadratic age effects did not survive multiple comparisons. When viewed across the full developmental period, white matter maturation is nonlinear (Lebel, Treit, & Beaulieu, ), but can appear linear when considering restricted age ranges. NDI has previously been shown to be more sensitive to age‐related change than diffusion measures (Genc, Malpas, et al, ), thus NDI may be sensitive enough to developmental processes to appropriately describe nonlinear white matter development occurring during adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most regions and measures showed linear trends, quadratic models outperformed linear models for MD in the splenium, and NDI in all regions except the right IFOF, right CST, and splenium, however, quadratic age effects did not survive multiple comparisons. When viewed across the full developmental period, white matter maturation is nonlinear (Lebel, Treit, & Beaulieu, ), but can appear linear when considering restricted age ranges. NDI has previously been shown to be more sensitive to age‐related change than diffusion measures (Genc, Malpas, et al, ), thus NDI may be sensitive enough to developmental processes to appropriately describe nonlinear white matter development occurring during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, FA was higher for males than females. Previous investigations of gender differences have been mixed, and many studies have identified no significant FA or MD differences between males and females (Bonekamp et al, ; Eluvathingal, Hasan, Kramer, Fletcher, & Ewing‐Cobbs, ; Giorgio et al, ; Uda et al, ), while other studies report significant gender differences in some brain regions, with inconsistent location and direction of differences (for review, see [Geeraert, Reynolds, & Lebel, in press; Lebel et al, ]). We also found an age‐by‐gender interaction for MD in the left uncinate such that MD decreased with age in boys but no relationship was observed in girls, as shown in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses of neuroimaging data enable the quantitative study of the human brain in health and disease . The mathematical characteristics of non‐scalar entities derived from dMRI data, such as the diffusion tensor (DT) or orientation distribution function (ODF), have led to exciting theoretical and computational developments.…”
Section: Statistics Of Local Diffusion Modelsmentioning
confidence: 99%
“…In adults, a reduction in FA due to the impact of malnutrition, dehydration, and weight loss (King, Frank, Thompson, & Ehrlich, 2017) might thus be more likely to occur compared with an increase in FA. The adolescent brain, on the other hand, is at a stage of rapid development (Lebel, Treit, & Beaulieu, 2017). The adolescent brain, on the other hand, is at a stage of rapid development (Lebel, Treit, & Beaulieu, 2017).…”
mentioning
confidence: 99%
“…The adolescent brain, on the other hand, is at a stage of rapid development (Lebel, Treit, & Beaulieu, 2017). As a result, white matter undergoes complex structural and architectural changes during adolescence (Lebel et al, 2017), and increases and decreases in FA can be observed at different stages and in different structures. As a result, white matter undergoes complex structural and architectural changes during adolescence (Lebel et al, 2017), and increases and decreases in FA can be observed at different stages and in different structures.…”
mentioning
confidence: 99%